Permeable polymer repairing anticorrosive adhesive cement

By optimizing the ratio and composition of powder and liquid materials in the permeable polymer repair anticorrosion glue, the problems of insufficient penetration capacity and waterproof and corrosion resistance of existing materials are solved, and efficient penetration and waterproof and corrosion resistance are achieved, which significantly improves the durability and strength of concrete.

CN119613046AInactive Publication Date: 2025-03-14TIANJIN JIANWEI ROAD & BRIDGE ENGINEERING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411800613.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the use of existing permeable concrete repair materials, the penetration capacity of the slurry is poor, and the waterproof and corrosion resistance after crystallization is also poor, which limits the widespread application of repair materials.

Method used

A permeable polymer repair anticorrosion slurry including powder material and liquid material is used. The powder material includes silicate cement, expansion agent, water reducing agent, crude aggregate, porous aggregate and modified mineral admixture, and the liquid material includes styrene butadiene emulsion, acrylate emulsion, preservative, defoaming agent, dispersant and antifreeze agent. By optimizing proportion and composition, the permeability and waterproof and corrosion resistance are improved.

Benefits of technology

The repaired anti-corrosion glue has excellent permeability and waterproof corrosion resistance, which can effectively block the micropores and cracks of concrete, improve the permeability and durability of concrete, enhance its compactness and strength, and also has good low temperature resistance, freeze-thaw resistance and anti-aging properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177962060000071
    Figure BDA0005177962060000071
  • Figure BDA0005177962060000081
    Figure BDA0005177962060000081
  • Figure BDA0005177962060000082
    Figure BDA0005177962060000082
Patent Text Reader

Abstract

The invention provides a permeable polymer repair anticorrosion adhesive cement, which comprises a powder material and a liquid material, the powder material comprises the following raw materials by mass: 35-50% of Portland cement, 1-3% of an expanding agent, 0.1-0.5% of a water reducing agent, 10-20% of a coarse aggregate, 10-20% of a porous aggregate, and 10-30% of a modified mineral admixture; the liquid material comprises the following raw materials in percentage by mass: 20-40% of styrene-butadiene emulsion, 20-40% of acrylate emulsion, 15-25% of a preservative, 1-5% of a defoaming agent, 5-10% of a dispersing agent and 5-10% of an anti-freezing agent. The anti-corrosion adhesive cement is high in infiltration capacity and has waterproof and anti-corrosion effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete repair, in particular to a permeable polymer repair anti-corrosion mortar. Background Art

[0002] In recent years, with the development and construction of cities, the construction of transportation projects has continued to increase, but concrete structures require regular care and maintenance, especially in coastal areas. Corrosion and damage to reinforced concrete are extremely common. Once problems occur in reinforced concrete, if they are not repaired in time, it is likely to bring immeasurable consequences and even extremely serious safety problems.

[0003] Concrete damage is mainly caused by the following reasons:

[0004] (1) Physical damage such as cracks, spalling, and wear caused by physical factors such as long-term loads, temperature changes, and freeze-thaw cycles. (2) Chemical erosion caused by corrosion such as acid rain, salt water, and chemicals. These chemicals will corrode the surface of concrete and reduce its strength and durability. (3) Biological activities such as plant root growth and microbial erosion can also cause damage to concrete structures. (4) Damage to concrete structures caused by natural disasters such as earthquakes and floods.

[0005] Different types of damage require different repair methods. Currently, the main repair methods for concrete damage are: (1) Surface repair method: Applicable to surface cracks with narrow crack width that have no effect on the structural bearing capacity. After cleaning the crack surface, fill it with materials such as cement mortar, epoxy putty or polymer repair mortar. (2) Grouting method: For cracks with a certain depth and width, pressure equipment is used to press the bonding material (such as epoxy resin, polyurethane, etc.) into the crack to fill the crack and enhance the integrity of the pavement. (3) Adding a covering layer method: Add a new layer of concrete or cement mortar on the damaged concrete floor to repair the damaged part. This method is suitable for repairing damage over a larger area. (4) Overall replacement method: For concrete structures that are severely damaged and cannot be repaired, overall replacement is required. This method is more expensive, but it can ensure the integrity and safety of the structure.

[0006] Penetrating concrete repair slurry is a kind of slurry that can penetrate into the micropores and cracks inside the concrete, fill the gaps and cracks and form water-insoluble crystals, plug the pores and cracks, improve the impermeability and durability of the concrete, thereby enhancing the density and strength of the concrete and achieving the repair effect. However, the penetrating repair materials currently on the market have poor penetration ability during use, and poor waterproof and anti-corrosion properties after crystallization and curing, which limits the wide application of repair materials. Summary of the invention

[0007] The purpose of the present invention is to provide a permeable polymer repair anti-corrosion mortar, which has strong permeability and waterproof and anti-corrosion effects.

[0008] The present invention solves the technical problem by adopting the following technical solutions.

[0009] The embodiment of the present invention provides a permeable polymer repair anti-corrosion mortar, including a powder material and a liquid material.

[0010] The powder material comprises the following raw materials by mass percentage: 35-50% silicate cement, 1-3% expansion agent, 0.1-0.5% water reducer, 10-20% coarse aggregate, 10-20% porous aggregate, and 10-30% modified mineral admixture;

[0011] The liquid material comprises the following raw materials by mass percentage: 20-40% of styrene-butadiene emulsion, 20-40% of acrylate emulsion, 15-25% of preservative, 1-5% of defoaming agent, 5-10% of dispersant and 5-10% of antifreeze agent.

[0012] In some embodiments of the present invention, the mass ratio of the liquid material to the powder material is 0.28-0.5.

[0013] In some embodiments of the present invention, the expansion agent is a mixture of calcium oxide and calcium sulfoaluminate, and the mass ratio of calcium oxide to calcium sulfoaluminate is 1:(1-2).

[0014] In some embodiments of the present invention, the water reducing agent is polycarboxylate phenol or polymethacrylate phenol.

[0015] In some embodiments of the present invention, the preservative includes one of sodium silicate or potassium silicate.

[0016] In some embodiments of the present invention, the porous aggregate is prepared by the following method: immersing porous alumina particles in a starch solution, then continuously introducing carbon dioxide gas for 10-20 hours, and drying and grinding to obtain the porous aggregate.

[0017] In some embodiments of the present invention, the modified mineral admixture is prepared by the following method: porous silica is mixed with tetraethyl orthosilicate, ultrasonically vibrated for 20-30 minutes, silica ash, fly ash, and zeolite powder are added, mixed evenly, and allowed to stand for 1-2 hours before solid-liquid separation to obtain the modified mineral admixture.

[0018] In some embodiments of the present invention, the antifreeze agent includes one or more of calcium chloride, calcium sulfate, calcium silicate, calcium aluminum silicate, and calcium aluminum magnesium silicate.

[0019] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0020] The repair anti-corrosion mortar provided by the present invention uses styrene-butadiene emulsion and acrylic ester emulsion as main components of liquid materials, and is used in combination with powder materials. The anti-corrosion mortar has excellent permeability and high long-term bonding strength with original concrete, and the two can be combined into a perfect body; secondly, the shrinkage rate of the anti-corrosion mortar after crystallization is small, and secondary voids and cracks will not be formed, and the anti-cracking performance is good; antifreeze agent is added to the liquid material, and the mortar crystals have excellent low-temperature resistance and good freeze-thaw resistance; the preservative can effectively prevent the penetration of chloride ions and carbon dioxide, prevent concrete carbonization and corrosion of internal steel bars; it has excellent anti-aging, salt spray and chemical corrosion resistance; the anti-corrosion mortar is simple to construct, does not affect the use of the original building during the structural reinforcement process, has no flatness requirements for the surface of the reinforced original building, and is convenient for node processing; the water-based product is non-toxic and environmentally friendly and can be widely used in engineering construction. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0022] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0023] The embodiment of the present invention provides a permeable polymer repair anti-corrosion mortar, including a powder material and a liquid material.

[0024] The powder material comprises the following raw materials by mass percentage: 35-50% silicate cement, 1-3% expansion agent, 0.1-0.5% water reducer, 10-20% coarse aggregate, 10-20% porous aggregate, and 10-30% modified mineral admixture;

[0025] The liquid material comprises the following raw materials by mass percentage: 20-40% of styrene-butadiene emulsion, 20-40% of acrylate emulsion, 15-25% of preservative, 1-5% of defoaming agent, 5-10% of dispersant and 5-10% of antifreeze agent.

[0026] The mass ratio of liquid material to powder material is 0.28-0.5.

[0027] The silicate cement is ultrafine cement with a grade of P·042.5, which is used as a cementitious material to provide strength. Preferably, the addition amount of silicate cement is 45%.

[0028] The expansion agent is a mixture of calcium oxide and calcium sulfoaluminate, and the mass ratio of calcium oxide to calcium sulfoaluminate is 1: (1-2); the water reducer is polycarboxylate phenol or polymethacrylate phenol. The expansion agent and the water reducer are used in combination, and have the properties of water reduction enhancement and anti-shrinkage, and can effectively improve the anti-cracking performance of the anti-corrosion mortar (mortar). Preferably, the optimal dosage of the expansion agent is 2.0%, and the optimal dosage of the water reducer is 0.3%.

[0029] The coarse aggregate is graded sand and gravel with a particle size of 1-3mm, of which 20-30% are sand and gravel with a particle size of 1-1.5mm, 20-30% are sand and gravel with a particle size of 1.5-2mm, 20-30% are sand and gravel with a particle size of 2-2.5mm, and 20-30% are sand and gravel with a particle size of 2.5-3mm. The surface of the sand and gravel particles needs to be wrapped with cement slurry, and the gaps between the sand and the sand should also be filled with cement slurry. The gaps between the coarse particles are filled with medium-sized sand and gravel, and the remaining gaps are filled with fine-grained sand and gravel to minimize the void ratio. At the same time, from the perspective of reducing the total surface area of ​​the aggregate particles and reducing the cement slurry used for wrapping, the particle size of the particles is preferably coarser. Therefore, the present invention starts from the porosity and total surface area of ​​the sand, and then combines the construction performance of the waterproof and repair mortar. The particle size of the graded sand and gravel can improve the construction performance of the waterproof and repair mortar and increase the density and strength of the mortar.

[0030] In the embodiment of the present invention, the porous aggregate used is prepared by the following method: porous alumina particles are soaked in a starch solution, and then carbon dioxide gas is continuously introduced for 10-20 hours, and the porous aggregate is obtained after drying and grinding. Porous alumina is used as a carrier, carbon dioxide is loaded in the porous structure, and then wrapped by starch to encapsulate a small amount of carbon dioxide in the porous structure. When the powder material and the liquid material are mixed, the starch on the surface dissolves, releasing the carbon dioxide in the porous structure, which can be combined with the free Ca(OH)2 in the silicate cement to form stable calcium carbonate, thereby improving the impermeability of the mortar, increasing the permeability of the mortar, and greatly reducing the intrusion of water and harmful substances.

[0031] In the embodiment of the present invention, the modified mineral admixture used is prepared by the following method: porous silica is mixed with tetraethyl orthosilicate, after ultrasonic oscillation for 20-30min, silica ash, fly ash, zeolite powder are added, mixed evenly, solid-liquid separation is performed after standing for 1-2h, and the modified mineral admixture is obtained. The modified mineral admixture is carried out with porous silica as a carrier, and under the action of ultrasonic oscillation, tetraethyl orthosilicate can be attached to the surface and inside of porous silica, and then silica ash and fly ash are added to wrap silica and tetraethyl orthosilicate, and the porous structure of zeolite powder can also adsorb a part of tetraethyl orthosilicate. When in use, tetraethyl orthosilicate hydrolyzes silicic acid, and silicic acid can be combined with free Ca (OH)2 to form calcium silicate compounds, which can improve the strength of mortar after crystallization, and after mortar crystallization, the residual tetraethyl orthosilicate continues to hydrolyze silicic acid in the presence of water, and reacts with free Ca (OH)2 in concrete, further repairs cracks, and realizes self-repair.

[0032] In the embodiment of the present invention, the preservative includes one of sodium silicate or potassium silicate. The antifreeze agent includes one or more of calcium chloride, calcium sulfate, calcium silicate, calcium aluminum silicate, and calcium aluminum magnesium silicate. The dispersant is one or more of sodium hexametaphosphate, potassium tripolyphosphate, and tetrapotassium pyrophosphate.

[0033] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0034] Examples 1-7

[0035] 1. Preparation of porous aggregate:

[0036] The porous alumina particles with a particle size of 100-200 nm are immersed in a starch aqueous solution with a mass fraction of 5%, and then carbon dioxide gas is continuously introduced for 10 hours, and then dried and ground to obtain the porous aggregate, wherein the mass ratio of the porous alumina to the starch is 3:1.

[0037] 2. Preparation of modified mineral admixtures:

[0038] By weight, 5 parts of porous silica and 3 parts of ethyl orthosilicate were mixed, and after ultrasonic vibration for 30 minutes, 2 parts of silica ash, 2 parts of fly ash and 2 parts of zeolite powder were added, mixed evenly, and allowed to stand for 2 hours before solid-liquid separation to obtain the modified mineral admixture.

[0039] 3. Prepare the raw materials of the anticorrosive mortar of this embodiment according to the following mass percentage ratio:

[0040] Powder material: Portland cement 45%, expansion agent 2%, water reducing agent (polycarboxylate phenol) 0.3%, coarse aggregate 20%, porous aggregate 10%, modified mineral admixture 22.7%;

[0041] The expansion agent is a mixture of calcium oxide and calcium sulfoaluminate, and the mass ratio of calcium oxide to calcium sulfoaluminate is 1:2. The coarse aggregate is composed of sand and gravel with the following particle sizes: 30% of sand and gravel with a particle size of 1-1.5mm, 30% of sand and gravel with a particle size of 1.5-2mm, 20% of sand and gravel with a particle size of 2-2.5mm, and 20% of sand and gravel with a particle size of 2.5-3mm.

[0042] Liquid material: 25% styrene-butadiene emulsion, 25% acrylate emulsion, 25% preservative (sodium silicate), 5% defoamer, 10% dispersant (sodium hexametaphosphate), 10% antifreeze (calcium sulfate). The defoamer is polyether defoamer B-364 produced by Guangdong Zhonglianban Fine Chemical Co., Ltd.

[0043] 4. Usage

[0044] (1) Pre-treat the surface to be repaired; the base surface should be solid, clean, and free of oil and other pollutants. The aged, cracked, loose, and severely oily structures should be thoroughly chiseled out until the base is clean and solid to ensure that the surface of the structure is solid and intact; if there is dust, the adhesion between the mortar and the base will be greatly reduced, so a high-pressure water washing machine should be used to thoroughly clean the foreign matter and ash layer left on the concrete surface.

[0045] (2) According to the mass ratio of liquid material to powder material of 0.22-0.40 (as shown in Table 1), slowly add the powder material into the liquid material while stirring and mix evenly. The storage time of the mixed mortar should not exceed 45 minutes. If the mixed mortar is not used in time and becomes dry and hard, it cannot be re-mixed with water and should be discarded.

[0046] (3) The mixed mortar is applied to the surface by manual pressure. The operation speed should be fast and the surface should be pressed in one direction. The surface should be smoothed once and pressed immediately to avoid repeated application. The thickness of each layer of plastering should be controlled within 3-5mm, and the time interval between each layer of plastering should be more than 10 hours. During construction, avoid harsh environmental conditions such as exposure to the sun, rain, and strong winds.

[0047] (4) Curing: After the mortar surface has finally set, sprinkle water manually and cover with plastic sheeting or wet sacks for curing. To avoid shrinkage cracks in the mortar, it should be cured in a moist environment for 7 days.

[0048] For the mortars with different proportions in the above step (2), a third-party testing agency was commissioned to test the performance of the mortars according to the standard of JC / T984-2011. The results are shown in Tables 1 and 2.

[0049] Table 1 Mechanical properties of mortars with different mix ratios

[0050]

[0051]

[0052] From Table 1 above, it can be concluded that with the increase of liquid material, the bonding strength and anti-seepage pressure of the waterproof mortar gradually increase, and the construction performance becomes better; when the ratio is greater than 0.35, the bonding strength and anti-seepage pressure begin to decrease, and the construction performance becomes worse. The strength becomes lower and lower with the increase of liquid material, and the compression ratio becomes lower and lower. Considering various properties, the best ratio of liquid material to powder material is 0.28-0.5. Among them, when the mass ratio of liquid material to powder material is 0.35, the comprehensive performance of the mortar is the best.

[0053] Table 2 Physical properties of mortars with different mix ratios

[0054]

[0055] It can be concluded from Table 2 that when the mix ratio of liquid to powder is 0.28-0.5, the mortar has excellent heat resistance and frost resistance, and its shrinkage, water absorption, initial setting time and final setting time all meet the JC / T984-2011 standard, and the comprehensive performance of the mortar is the best.

[0056] Example 8

[0057] The difference from Example 1 is that the ratio of the liquid material to the powder material is different, as shown below:

[0058] Powder material: 50% silicate cement, 2.5% expansion agent, 0.5% water reducer (polycarboxylate phenol), 20% coarse aggregate, 10% porous aggregate, 17% modified mineral admixture;

[0059] Liquid material: 30% styrene-butadiene emulsion, 20% acrylate emulsion, 25% preservative (sodium silicate), 5% defoaming agent, 10% dispersant (sodium hexametaphosphate), 10% antifreeze agent (calcium sulfate).

[0060] The types of raw materials are the same as those in Example 1.

[0061] Example 9

[0062] The difference from Example 1 is that the ratio of the liquid material to the powder material is different, as shown below:

[0063] Powder material: Portland cement 35%, expansion agent 3%, water reducing agent (polycarboxylate phenol) 0.5%, coarse aggregate 20%, porous aggregate 11.5%, modified mineral admixture 30%;

[0064] Liquid material: 40% styrene-butadiene emulsion, 20% acrylate emulsion, 15% preservative (sodium silicate), 5% defoaming agent, 10% dispersant (sodium hexametaphosphate), 10% antifreeze agent (calcium sulfate).

[0065] The types of raw materials are the same as those in Example 1.

[0066] Example 10

[0067] The difference from Example 1 is that the expansion agent is a mixture of calcium oxide and calcium sulfoaluminate, and the mass ratio of calcium oxide to calcium sulfoaluminate is 1: 1. The proportions of the raw materials of the liquid material and the proportions of the raw materials of the powder material are the same as those of Example 1.

[0068] Embodiment 11

[0069] The difference from Example 1 is that the coarse aggregate is composed of sand and gravel with the following particle sizes: 20% of sand and gravel with a particle size of 1-1.5 mm, 20% of sand and gravel with a particle size of 1.5-2 mm, 30% of sand and gravel with a particle size of 2-2.5 mm, and 30% of sand and gravel with a particle size of 2.5-3 mm. The proportions of the raw materials of the liquid material and the proportions of the raw materials of the powder material are the same as those of Example 1.

[0070] To sum up, the repair anti-corrosion mortar provided by the present invention uses butadiene-styrene emulsion and acrylic ester emulsion as the main components of the liquid material, and is used in combination with a powder material. The anti-corrosion mortar has excellent permeability and high long-term bonding strength with the original concrete, and the two can be combined into a perfect body; secondly, the anti-corrosion mortar has small shrinkage after crystallization and good anti-cracking performance; antifreeze is added to the liquid raw material, and the mortar crystals have excellent low-temperature resistance and good freeze-thaw resistance; the preservative can effectively prevent the penetration of chloride ions and carbon dioxide, prevent concrete carbonization and corrosion of internal steel bars; it has excellent anti-aging, salt spray and chemical corrosion resistance; the anti-corrosion mortar is easy to construct, does not affect the use of the original building during the structural reinforcement process, has no flatness requirements for the surface of the reinforced original building, and is convenient for node processing; the water-based product is non-toxic and environmentally friendly and can be widely used in engineering construction.

[0071] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. Penetration type polymer repair anti-corrosion mortar, characterized in that: Including powder and liquid materials, The powder material includes the following raw materials by mass percentage: Portland cement 35-50%, expansion agent 1-3%, water reducer 0.1-0.5%, coarse aggregate 10-20%, porous aggregate 10-20%, modified mineral admixture 10-30%; The liquid material comprises the following raw materials by mass percentage: Butadiene-styrene emulsion 20-40%, acrylic emulsion 20-40%, preservative 15-25%, defoamer 1-5%, dispersant 5-10%, antifreeze 5-10%.

2. The penetrating polymer repair anticorrosive mortar according to claim 1 is characterized in that: The mass ratio of the liquid material to the powder material is 0.28-0.

5.

3. The penetrating polymer repair anticorrosive mortar according to claim 1 is characterized in that: The expansion agent is a mixture of calcium oxide and calcium sulfoaluminate, and the mass ratio of calcium oxide to calcium sulfoaluminate is 1:(1-2).

4. The penetrating polymer repair anticorrosive mortar according to claim 1 is characterized in that: The water reducing agent is polycarboxylate phenol or polymethacrylate phenol.

5. The penetrating polymer repair anticorrosive mortar according to claim 1 is characterized in that: The preservative includes one of sodium silicate or potassium silicate.

6. The penetrating polymer repair anticorrosive mortar according to claim 1, characterized in that: The porous aggregate is prepared by the following method: The porous alumina particles are immersed in a starch solution, and then carbon dioxide gas is continuously introduced for 10-20 hours. After drying and grinding, the porous aggregate is obtained.

7. The penetrating polymer repair anticorrosive mortar according to claim 1 is characterized in that: The modified mineral admixture is prepared by the following method: The porous silica is mixed with ethyl orthosilicate, and after ultrasonic vibration for 20-30 minutes, silica fume, fly ash and zeolite powder are added, mixed evenly, and solid-liquid separation is performed after standing for 1-2 hours to obtain the modified mineral admixture.

8. The penetrating polymer repair anticorrosive mortar according to claim 1 is characterized in that: The antifreeze agent includes one or more of calcium chloride, calcium sulfate, calcium silicate, calcium aluminum silicate, and calcium aluminum magnesium silicate.

Citation Information

Patent Citations

  • Modified cement slurry for rapidly repairing concrete

    CN105130314A

  • Quick repair mortar for high-speed railway concrete track slab and preparation method thereof

    CN111533517A

  • Permeation cross-linking type reinforcing anti-corrosion material for concrete cooling tower and application thereof

    CN113248200A

  • Impermeable self-compacting concrete and preparation method thereof

    CN113526927A

  • High polymer duct grouting material and preparation method thereof

    CN114772999A